Analysis of Temperature During Storage and the Period of Warm Ischemia of the Graft in Kidney Transplants - Carminati Lima, André; Carpilovsky Revoredo Alves, Juliana; Borga, Ana Lavratti; Ocampos, Henrique Brambilla de Lucca; Deboni, Luciane Mônica; Guterres, Jean Cristovão Pereira; Garcia, Christian Evangelista (Brazilian Journal of Transplantation, 2023)
Objective: This study aims to analyze the temperatures of kidney transplants performed at Hospital Municipal São José, Joinville/SC, throughout the period of cold ischemia and whether this temperature is in line with what is recommended in the literature. Method: Prospective analysis based on all kidney grafts that was used for kidney transplant in the unit of kidney transplant of Hospital Municipal São José. Results: The study analyzed that the current method of graft conservation partially meets the expected values, to maintain the recommended temperature. Conclusion: It is important to maintain studies and analyzes on the subject for continuous improvement in graft storage.